Analysis of the dura involvement in cholesteatoma surgery. - Schwarz, David; Gostian, Antoniu-Oreste; Shabli, Sami; Wolber, Philipp; Huettenbrink, Karl Bernd; Anagiotos, Andreas (Auris Nasus Larynx, 2018)
The involvement of the dura is a rare yet potentially life-threatening complication during cholesteatoma surgery. Thus, the knowledge about treatment and consequences of this issue is of great importance to every ear surgeon.This retrospective study analyzed the dura involvement with regard to the type of defect, reconstruction method used, and the post-operative complications of 1291 pediatric and adult cholesteatoma surgeries performed at an academic tertiary care center over a twelve-year period.From a total of 1291 cholesteatoma surgeries, we identified 84 patients (6.5%) with dura involvement intraoperatively, most of them adult patients. The majority of the reported cases were bony defects and exposed dura without CSF leakage (79.73%, 67 out of 84). In 14.28% of the cases (12 out of 84) a meningo(encephalo)cele or dura defect with liquorrhea were detected. In 30 surgeries (35.7%, 30 out of 84) no reconstruction of the lateral skull base was considered necessary. The most common material used for reconstruction was conchal cartilage (25.0%, 21 out of 84), followed by polydioxanone (PDS)-foil (11.9%, 10 out of 84), bone pâté (9.5%, 8 out of 84) and a combination of materials (17.9%, 15 out of 84). Revision surgery of the reconstruction was necessary in 16.7% (14 out of 84) of the cases. Long-term evaluation (mean of 19.3 months) showed no complication related to the skull base defect.During cholesteatoma surgery, bony and dura defects can be managed effectively, with good long-term reliability. No intracranial or mastoidal complications are expected.
EVALuna2:245920